Composite welding method for a heat sink

CN122913713APending Publication Date: 2026-10-16WTP TECH (SU ZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611243339.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]现有散热器焊接后的校形和检测通常采用简单的人工敲击校形和水浸气泡检漏,校形精度低,检测灵敏度不足,微小泄漏难以检出,散热器的出厂合格率受限

Benefits of technology

[0037] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122913713A_ABST
    Figure CN122913713A_ABST
Patent Text Reader

Abstract

The application discloses a composite welding method of a radiator, and belongs to the technical field of welding. The method comprises the following steps: performing surface pretreatment on a radiator substrate to be welded, a flow channel spacer and a cover plate, including alkaline degreasing, acid pickling activation, water washing and drying; laying Al-Si-Mg series filler metal sheets between the flow channel spacer and the substrate and the cover plate, controlling the assembly gap to be 0.05-0.10 mm and pressing and positioning; and performing flat plate pressing and correcting, cleaning, air tightness detection and double sealing property detection of a helium mass spectrum leak detection on the radiator semi-finished product. Through the composite process of vacuum brazing and laser edge sealing welding, the application realizes the cooperation of precise sealing of the internal flow channel of the radiator and high-strength sealing of the outer edge, and improves the overall sealing reliability and welding quality consistency of the radiator.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of welding technology, and in particular to a composite welding method for radiators. Background Technology

[0002] Heat sinks are critical components for heat management in electronic equipment, new energy vehicles, and power electronics. The sealing and thermal conductivity of their internal flow channel structure directly affect heat dissipation efficiency and equipment reliability. Current heat sink manufacturing typically employs a single welding process, such as vacuum brazing or laser welding. However, a single welding process cannot simultaneously meet the dual requirements of the complex internal flow channel structure and the sealing of the outer edge of the heat sink.

[0003] Current methods for sealing internal flow channels in radiators typically employ vacuum brazing, where the filler metal melts and fills the gaps between mating surfaces to achieve a connection. However, the weld seam in vacuum brazing is located inside the radiator, and the filler metal filling at the outer edge joint is insufficient, posing a risk of leakage. Furthermore, the strength of the brazed joint is limited, making it prone to failure under high internal pressure or mechanical loads. Existing methods do not provide supplementary sealing for the brazed outer edge joint, resulting in insufficient overall sealing reliability of the radiator.

[0004] Existing radiator outer edge seals are usually achieved using laser welding or argon arc welding. However, when laser welding is performed directly on the untreated aluminum alloy surface, the surface oxide film and oil stains result in high weld porosity and poor forming. Furthermore, the internal flow channel structure of the radiator is complex, and improper control of the heat input during laser welding can easily lead to remelting of the internal brazed joints or deformation of the flow channel ribs, affecting the accuracy of the internal flow channel.

[0005] In existing radiator brazing processes, the brazing filler metal is typically laid out using a simple covering method, with the edges of the filler metal flush with or extending beyond the mating surface. During brazing, excess filler metal overflows, forming weld beads that affect subsequent assembly and appearance quality. Insufficient filler metal coverage can lead to localized missing filler metal on the mating surface, resulting in seal failure. Current methods do not precisely control the filler metal coverage area and edge indentation, leading to inconsistent brazing quality.

[0006] Existing vacuum brazing temperature profiles for radiators typically use a single heating rate to directly reach the brazing temperature without an intermediate holding plateau. The oxide film on the aluminum alloy surface begins to decompose in the 300-350℃ range. Direct and rapid heating leads to insufficient decomposition of the oxide film and reduced wettability of the brazing filler metal. Furthermore, rapid heating causes a large temperature difference between the inside and outside of the workpiece, resulting in concentrated thermal stress, which can easily cause warping and deformation in large-sized radiators.

[0007] Before laser edge sealing welding of existing radiators, the outer edge joints are usually not repaired, resulting in large gaps and misalignments. This makes it difficult for the liquid metal to fill during laser welding, leading to frequent incomplete penetration or undercut defects at the weld root. Furthermore, residual oxide film and impurities on the outer edge joint surface cause porosity and slag inclusions in the weld. Existing methods lack established standards for the repair and cleaning of outer edge joints, resulting in inconsistent laser welding quality.

[0008] The current method of straightening and testing radiators after welding usually involves simple manual tapping and water immersion for leak detection. This method has low straightening accuracy and insufficient detection sensitivity, making it difficult to detect minute leaks and limiting the factory pass rate of radiators. Summary of the Invention

[0009] Therefore, embodiments of the present invention provide a composite welding method for heat sinks.

[0010] On the one hand, a composite welding method for a heat sink is provided, comprising the following steps:

[0011] S1, perform surface pretreatment on the heat sink substrate, flow channel ribs and cover plate to be welded, the surface pretreatment includes alkaline washing and degreasing, acid washing and activation, water washing and drying in sequence;

[0012] S2, the brazing filler metal sheet is laid between the flow channel baffle and the radiator substrate and between the flow channel baffle and the cover plate. The radiator substrate, flow channel baffle, brazing filler metal sheet and cover plate are assembled and pressed into position according to the flow channel structure to obtain the assembly to be welded. The assembly gap between each brazing mating surface is 0.05 to 0.10 mm.

[0013] S3. Place the assembly to be welded into the vacuum brazing furnace, evacuate the vacuum, heat it to the brazing temperature according to the preset temperature curve and keep it at the temperature. After the brazing filler metal melts, it fills each brazing mating surface. After cooling with the furnace, it is taken out to obtain an intermediate body with the flow channel sealing surface completed by brazing connection.

[0014] S4, laser sealing welding is performed on the outer edge seam of the intermediate body. Under the protection of inert gas, welding is continuously performed along the outer edge seam, and a sealing weld is formed between the outer edge of the radiator substrate and the cover plate to obtain the radiator semi-finished product.

[0015] S5 involves shaping, cleaning, and sealing testing of the semi-finished radiator. Once the sealing test is passed, the finished radiator is obtained.

[0016] Furthermore, in step S1, the alkaline washing and degreasing uses a sodium hydroxide solution with a concentration of 40-60 g / L, a treatment temperature of 50-65℃, and a treatment time of 3-8 min;

[0017] Acid washing and activation are performed using a 10%–15% (v / v) nitric acid solution at room temperature for 1–3 min.

[0018] The drying temperature is 80-120℃, the drying time is 20-40 minutes, and the time interval between drying and assembly in step S2 does not exceed 24 hours.

[0019] Furthermore, the heat sink base plate and cover plate are made of 3003 aluminum alloy;

[0020] In step S2, the solder sheet is an Al-Si-Mg based aluminum solder sheet with a thickness of 0.08–0.12 mm.

[0021] The area of ​​the brazing filler metal sheet shall not be less than 95% of the area of ​​the corresponding brazing mating surface, and the edge of the brazing filler metal sheet shall be recessed by 0.5 to 1.0 mm relative to the edge of the corresponding brazing mating surface.

[0022] Furthermore, in step S3, the vacuum level inside the vacuum brazing furnace is no higher than 5 × 10⁻⁶. -3 Pa;

[0023] The preset temperature curve is as follows: heat up to 300-350℃ at a first heating rate of 5-10℃ / min and hold for 15-30min, then heat up to the brazing temperature at a second heating rate of 3-6℃ / min and hold for 10-25min.

[0024] The brazing temperature is 33-53℃ lower than the solidus temperature of 3003 aluminum alloy, and the brazing temperature is 590-610℃.

[0025] Furthermore, the furnace is first cooled to 480-520℃ and held for 10-20 minutes, then cooled to the furnace outlet temperature before being removed from the furnace. The outlet temperature should not exceed 150℃.

[0026] Furthermore, the laser edge sealing welding uses a fiber laser with a focused spot diameter of 0.4–0.5 mm, a laser power of 2000–3000 W, a welding speed of 35–60 mm / s, and a defocusing amount of -1–+1 mm.

[0027] The inert gas is argon or helium, and the protective gas flow rate is 15–30 L / min.

[0028] Furthermore, before laser edge sealing welding, the outer edge joint of the intermediate body is trimmed: the two sides of the outer edge joint are milled by 0.3 to 0.8 mm to ensure that the fit gap of the outer edge joint is no more than 0.10 mm and the misalignment is no more than 0.05 mm.

[0029] After repair, the outer edge seams are scraped and cleaned. The time interval between scraping and cleaning and laser edge sealing welding shall not exceed 2 hours.

[0030] Furthermore, the protective gas is delivered from a nozzle with a diameter of 6-8 mm, the angle between the nozzle axis and the welding direction is 30-45°, the distance between the nozzle outlet and the outer edge joint is 10-15 mm, and the gas velocity at the nozzle outlet is 8-12 m / s.

[0031] Furthermore, in step S2, a graphite pressure plate is used for clamping and positioning. A clamping pressure of 0.05 to 0.15 MPa is applied to each part to be welded by the graphite pressure plate, and the contact surface between the graphite pressure plate and the part to be welded is coated with boron nitride solder resist.

[0032] Furthermore, in step S5:

[0033] The calibration is performed using a flat plate, and the flatness of the mounting surface of the radiator semi-finished product after calibration is no more than 0.2mm.

[0034] The airtightness test includes airtightness testing and helium mass spectrometry leak detection. The airtightness test is performed by introducing dry gas at a pressure of 0.6 to 0.9 MPa into the flow channel, holding the pressure for 240 to 360 seconds, and determining that the airtightness test is qualified if the pressure drop is not greater than 600 Pa.

[0035] The leak rate of helium mass spectrometry leak detection is no greater than 1×10⁻⁶. -7 Pa·m 3 / s indicates that the helium mass spectrometry leak detection is qualified.

[0036] Beneficial effects

[0037] The beneficial effects of the technical solutions provided in the embodiments of the present invention include at least the following:

[0038] After activation, washing, and drying, brazing filler metal sheets are laid between the flow channel baffles and the radiator substrate, as well as between the flow channel baffles and the cover plate. The assembly is then assembled and pressed into position according to the flow channel structure to obtain the assembly to be welded. After being placed in a vacuum brazing furnace and evacuated, the assembly is heated to the brazing temperature according to the preset temperature curve and held at that temperature. After the brazing filler metal sheets melt, they fill each brazing mating surface. After cooling in the furnace, the assembly is removed to obtain an intermediate body. The outer edge joint of the intermediate body is then laser-sealed. Under inert gas protection, continuous welding is performed along the outer edge joint to form a sealed weld. This solves the technical problem in the existing technology where it is difficult to simultaneously meet the dual requirements of the complex internal flow channel structure and the outer edge sealing when using a single welding process. It achieves the composite welding technology effect of achieving precise sealing of the internal flow channel through vacuum brazing and high-strength sealing of the outer edge through laser-sealed edge welding.

[0039] This invention solves the technical problems in the prior art where insufficient brazing area leads to local missing solder or excessive solder overflow due to excessive edge extension. By controlling the brazing filler metal sheet to be an Al-Si-Mg based aluminum-based sheet with a thickness of 0.08-0.12 mm, the brazing filler metal sheet's laying area is not less than 95% of the area of ​​the corresponding brazing mating surface, and the edge of the brazing filler metal sheet is recessed by 0.5-1.0 mm relative to the edge of the corresponding brazing mating surface, this invention achieves the technical effect of precisely controlling the brazing filler metal sheet's laying area and the amount of edge recess, avoiding solder overflow, and ensuring complete filling of the mating surface.

[0040] This invention solves the technical problems of insufficient oxide film decomposition and workpiece thermal stress concentration caused by direct heating at a single heating rate in the prior art, which is 33-53°C lower than the solidus temperature of 3003 aluminum alloy. It achieves the technical effects of promoting oxide film decomposition through an intermediate holding platform, reducing thermal stress through segmented heating, and avoiding overheating of the base material through a brazing temperature lower than the solidus temperature. Attached Figure Description

[0041] Figure 1 A flowchart provided for an embodiment of this application. Detailed Implementation

[0042] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0043] like Figure 1 As shown, a composite welding method for a radiator includes the following steps:

[0044] S1, perform surface pretreatment on the heat sink substrate, flow channel ribs and cover plate to be welded, the surface pretreatment includes alkaline washing and degreasing, acid washing and activation, water washing and drying in sequence;

[0045] S2, the brazing filler metal sheet is laid between the flow channel baffle and the radiator substrate and between the flow channel baffle and the cover plate. The radiator substrate, flow channel baffle, brazing filler metal sheet and cover plate are assembled and pressed into position according to the flow channel structure to obtain the assembly to be welded. The assembly gap between each brazing mating surface is 0.05 to 0.10 mm.

[0046] S3. Place the assembly to be welded into the vacuum brazing furnace, evacuate the vacuum, heat it to the brazing temperature according to the preset temperature curve and keep it at the temperature. After the brazing filler metal melts, it fills each brazing mating surface. After cooling with the furnace, it is taken out to obtain an intermediate body with the flow channel sealing surface completed by brazing connection.

[0047] S4, laser sealing welding is performed on the outer edge seam of the intermediate body. Under the protection of inert gas, welding is continuously performed along the outer edge seam, and a sealing weld is formed between the outer edge of the radiator substrate and the cover plate to obtain the radiator semi-finished product.

[0048] S5 involves shaping, cleaning, and sealing testing of the semi-finished radiator. Once the sealing test is passed, the finished radiator is obtained.

[0049] It should be noted that:

[0050] The cooling channels of the radiator are formed by channel ribs connected to the radiator base plate and cover plate, resulting in numerous connection nodes and thin-walled, narrow mating surfaces. Furthermore, the outer edge seams require continuous, sealed welds. This solution implements the connection in two steps: first, brazing all channel sealing surfaces in a vacuum environment; then, laser edge sealing welding is performed on the brazed intermediate body. Vacuum brazing involves overall furnace heating, with all mating surfaces of the assembly reaching brazing temperature simultaneously, and all connection nodes completed in a single heating process. Laser edge sealing welding involves localized heating, acting only on the outer edge seams. If laser edge sealing welding is performed first, and then the intermediate body is brazed as a whole in the furnace, the outer edge weld metal softens at the brazing temperature. The difference in heating rate between the outer edge weld and the base material during the furnace heating stage will generate additional thermal stress in the weld. Simultaneously, the sealed outer edge weld hinders the escape of gas from the channels during the vacuuming stage. Therefore, laser edge sealing welding is performed after vacuum brazing.

[0051] The assembly gap range is determined as follows: After clamping and positioning, residual flatness error still exists on each brazed mating surface. This error, based on the cover plate flatness tolerance and the springback after clamping, is statistically estimated to be 0.04–0.05 mm. The assembly gap must be greater than the residual flatness error for the molten brazing filler metal to fill the channel. Therefore, the lower limit of the assembly gap is 0.05 mm. When the assembly gap is greater than 0.10 mm, the capillary holding force is insufficient to restrain the molten brazing filler metal, which flows away under gravity, resulting in unfilled areas on the mating surfaces. This limit is determined by the brazing filler metal filling test. Therefore, the upper limit of the assembly gap is 0.10 mm.

[0052] As an optional embodiment, in step S1, the alkaline washing and degreasing uses a sodium hydroxide solution with a concentration of 40-60 g / L, the treatment temperature is 50-65°C, and the treatment time is 3-8 min;

[0053] Acid washing and activation are performed using a 10%–15% (v / v) nitric acid solution at room temperature for 1–3 min.

[0054] The drying temperature is 80-120℃, the drying time is 20-40 minutes, and the time interval between drying and assembly in step S2 does not exceed 24 hours.

[0055] It should be noted that:

[0056] Alkaline degreasing is used to dissolve the natural oxide film on the surface of the parts to be welded and remove processing grease. The treatment time is determined according to the dissolution process of the oxide film, and the calculation formula is as follows:

[0057]

[0058] In the formula, This refers to the alkaline washing treatment time. The calculated thickness of the natural oxide film and surface adsorption layer is taken as 8–12 nm. The dissolution rate of the oxide film by sodium hydroxide solution was measured to be 1.5–2.5 nm / min under conditions of concentration 40–60 g / L and temperature 50–65 °C. Substituting these values ​​into the calculation, the processing time was 3.2–8 min, and we took 3–8 min as the range.

[0059] Pickling activation is used to neutralize the residual alkali solution on the surface after alkaline washing and to dissolve the silicon-containing oxide residue that cannot be removed during the alkaline washing process. The volume fraction of nitric acid is determined by an oxide residue dissolution test; when the volume fraction is below 10%, the oxide residue is not completely dissolved, and when the volume fraction is above 15%, the substrate corrosion rate increases. After drying, the surface of the part to be welded is in an activated state, and the natural oxide film regenerates in air according to a parabolic law. The formula for calculating the time required for regeneration to reach the critical thickness affecting brazing wetting is:

[0060]

[0061] In the formula, The time required for the oxide film to regenerate to the critical thickness. To determine the critical oxide film thickness affecting brazing wetting, a value of 15 nm was chosen. The oxide film growth rate constant is 9–10 nm, measured in an environment with a relative humidity not exceeding 60%. 2 / h. Substitute into the calculation, The drying time is 22.5 to 25 hours, therefore the time interval between drying and assembly should not exceed 24 hours.

[0062] As an optional embodiment, the heat sink base plate and cover plate are made of 3003 aluminum alloy;

[0063] In step S2, the solder sheet is an Al-Si-Mg based aluminum solder sheet with a thickness of 0.08–0.12 mm.

[0064] The area of ​​the brazing filler metal sheet shall not be less than 95% of the area of ​​the corresponding brazing mating surface, and the edge of the brazing filler metal sheet shall be recessed by 0.5 to 1.0 mm relative to the edge of the corresponding brazing mating surface.

[0065] It should be noted that:

[0066] The liquidus temperature of Al-Si-Mg aluminum-based brazing filler metals is lower than the solidus temperature of 3003 aluminum alloy. Silicon is used to lower the melting temperature of the filler metal and improve its fluidity. Magnesium evaporates and reduces the oxide film on the surface of the workpiece under vacuum. The thickness of the filler metal sheet is determined by the amount of filler metal required to fill the weld seam, calculated as follows:

[0067]

[0068]

[0069] In the formula, For the thickness of the solder sheet, The midpoint of the assembly clearance design range is taken as 0.075mm. This is the brazing filler metal compensation coefficient. The filler metal's percentage of the brazed mating surfaces, determined by a filler metal test, is 0.85. The solder retention rate, after deducting overflow loss, is 0.90 as determined by the overflow test. Substituting this into the calculation... It is 1.31. The thickness is 0.098 mm, and the standard thickness of the solder sheet is 0.08 to 0.12 mm.

[0070] The inward shrinkage of the solder edge is determined based on the maximum spread distance of the molten solder. The molten solder spreads outward along the mating surface, with the spread distance determined by the spreading test to be 0.3–0.8 mm. The inward shrinkage is 0.5–1.0 mm. The molten solder spreads to the edge of the mating surface without flowing outward to the non-mating surface. The spread area is not less than 95% of the mating surface area to ensure that each mating surface receives sufficient solder.

[0071] As an optional embodiment, in step S3, the vacuum degree inside the vacuum brazing furnace is not higher than 5 × 10⁻⁶. -3 Pa;

[0072] The preset temperature curve is as follows: heat up to 300-350℃ at a first heating rate of 5-10℃ / min and hold for 15-30min, then heat up to the brazing temperature at a second heating rate of 3-6℃ / min and hold for 10-25min.

[0073] The brazing temperature is 33-53℃ lower than the solidus temperature of 3003 aluminum alloy, and the brazing temperature is 590-610℃.

[0074] It should be noted that:

[0075] The vacuum level is determined based on the control requirements of the oxygen partial pressure in the residual gas. During the heating process, the formation rate of the oxide film on the aluminum surface increases with increasing oxygen partial pressure. To suppress oxide film regeneration, the oxygen partial pressure in the residual gas must not exceed the critical oxygen partial pressure. The formula for calculating the vacuum level is:

[0076]

[0077] In the formula, The vacuum level inside the vacuum brazing furnace. To suppress the regeneration of the oxide film on the aluminum surface, the critical oxygen partial pressure is set to 1.2 × 10⁻⁶. -3 Pa, Let be the volume fraction of oxygen in the residual gas, taken as 0.2095. Substitute this into the calculation. It is 5.7 × 10 -3Considering the measurement error of the vacuum gauge, the vacuum level should not exceed 5 × 10 Pa. -3 Pa.

[0078] In the first heating stage, a holding platform is set at 300–350℃. Gases and residual moisture adsorbed on the surface of the parts to be welded are released in this temperature range. The holding period continues until the furnace pressure drops to less than 1.5 times the level at the end of vacuuming. This process, according to experimental statistics, takes 15–30 minutes. The temperature in the first heating stage is below the melting temperature of the brazing filler metal, and the first heating rate is 5–10℃ / min. In the second heating stage, the temperature is close to the brazing temperature, and the second heating rate is reduced to 3–6℃ / min. This is used to control the cross-sectional temperature difference of the assembly and prevent local temperatures from exceeding the solidus temperature of the base metal. The brazing temperature is determined based on the solidus temperature of the base metal, calculated using the following formula:

[0079]

[0080] In the formula, For brazing temperature, The solidus temperature of 3003 aluminum alloy is taken as 643℃. To prevent melting of the grain boundaries of the base material, a safe temperature range of 33–53℃ is used. Substituting this into the calculation, the brazing temperature is 590–610℃.

[0081] The heat preservation time is determined by the superposition of the workpiece heat penetration time and the interface bonding time. Based on temperature measurement tests, the workpiece heat penetration time is 8–15 minutes, provided the temperature difference between each measuring point on the assembly and the set temperature is no greater than 5°C. The filling process of the molten brazing filler metal is calculated using a capillary spread model, and the formula is:

[0082]

[0083] In the formula, For the time of grouting, To determine the viscosity of the molten solder, take 1.0 × 10⁻⁶. -3 Pa·s, The distance the brazing filler metal spreads along the mating surface is taken as 15mm. The surface tension of the molten solder is taken as 0.85 N / m. The radius of the capillary channel is taken as half of the assembly gap. The wetting angle is taken as 30°. Substituting this into the calculation, the caulking process is completed in seconds. The interfacial metallurgical bonding time is statistically estimated to be 2–10 min based on element diffusion experiments; therefore, the holding time is taken as 10–25 min.

[0084] As an optional embodiment, the furnace cooling in step S3 includes: first cooling the furnace to 480-520°C and holding it at that temperature for 10-20 minutes, then cooling the furnace to the furnace exit temperature and removing the furnace, with the furnace exit temperature not exceeding 150°C.

[0085] It should be noted that:

[0086] After brazing and heat preservation, the assembly is in a high-temperature, low-strength state. Direct cooling will cause thermal stress due to the temperature difference across the cross-section, leading to deformation of the thin-walled flow channel structure. A heat preservation platform is installed during furnace cooling to 480–520℃ to reduce the temperature difference across the assembly cross-section to below 10K. The formula for calculating the thermal stress caused by this temperature difference is:

[0087]

[0088] In the formula, Thermal stress caused by temperature difference across the cross section The elastic modulus of the aluminum alloy is taken as 7.0 × 10⁻⁶. 4 MPa Let be the coefficient of linear expansion of the aluminum alloy, taken as 23.6 × 10⁻⁶. -6 / K, The corresponding cross-sectional temperature difference is taken as 10K. Substitute this into the calculation. The yield strength is 16.5 MPa, which is 20-30 MPa lower than the yield strength of 3003 aluminum alloy in the 480-520℃ range. The assembly does not undergo plastic deformation under this temperature difference. The process of the cross-sectional temperature difference decreasing to within 10K from the start of heat preservation, as measured by temperature statistics, takes 10-20 minutes. When the furnace exit temperature exceeds 150℃, the cooling rate of the assembly in air increases, and the proportion of thermal stress microcracks appearing at the brazing seam edges rises. This limit was determined by comparative tests of furnace exit temperatures; therefore, the furnace exit temperature is set not to exceed 150℃.

[0089] As an optional embodiment, in step S4:

[0090] Laser edge sealing welding uses a fiber laser with a focused spot diameter of 0.4–0.5 mm, a laser power of 2000–3000 W, a welding speed of 35–60 mm / s, and a defocusing amount of −1–+1 mm.

[0091] The inert gas is argon or helium, and the protective gas flow rate is 15–30 L / min.

[0092] It should be noted that:

[0093] The laser power and welding speed are matched according to the required linear energy of the outer edge joint. The penetration depth of the outer edge joint must be no less than 2mm of the cover plate thickness. The formula for calculating the linear energy is:

[0094]

[0095] In the formula, For line energy, To account for the correction factor caused by the high thermal conductivity of aluminum, a value of 16–26 is used. The density of the aluminum alloy is taken as 2700 kg / m³. 3, The specific heat capacity of the aluminum alloy is taken as 900 J / (kg·K). The corresponding temperature difference is the difference between room temperature and the melting point, taken as 635K. The latent heat of fusion of the aluminum alloy is taken as 3.97 × 10⁻⁶. 5 J / kg, The width of the melting zone is 0.5 mm. For the penetration depth, we take 2mm. Substituting into the calculation, the minimum melting energy per unit length is 2.6J / mm, and the corrected linear energy is 42–68J / mm, taking 40–65J / mm. The welding speed is determined according to the relationship between linear energy and laser power, calculated as follows:

[0096]

[0097] In the formula, For welding speed, The laser power is set to 2000–3000 W. The linear energy is taken as 40–65 J / mm. Substituting this into the calculation, the welding speed is 31–75 mm / s, taken as 35–60 mm / s. The defocusing amount is adjusted within the range of −1 to +1 mm to keep the focused spot diameter at 0.4–0.5 mm, and to keep the width and depth of the molten zone stable.

[0098] As an optional embodiment, before performing laser edge sealing welding, the step of trimming the outer edge joint of the intermediate body is also included: milling 0.3 to 0.8 mm on both sides of the outer edge joint so that the fitting gap of the outer edge joint is no more than 0.10 mm and the misalignment is no more than 0.05 mm.

[0099] After repair, the outer edge seams are scraped and cleaned. The time interval between scraping and cleaning and laser edge sealing welding shall not exceed 2 hours.

[0100] It should be noted that:

[0101] During vacuum brazing, molten filler metal flows to the vicinity of the outer edge joint, leaving behind filler metal accumulation and oxidation products. Milling is used to remove these residues and obtain a regular joint cross-section. The milling amount is determined based on the filler metal flow distance and oxide layer depth, ranging from 0.3 to 0.8 mm. The upper limit of the fit clearance is determined based on the focused spot diameter, calculated as follows:

[0102]

[0103] In the formula, This refers to the allowable clearance for the outer edge joint. The diameter of the focused spot is taken as 0.4 mm. Substituting this into the calculation, the upper limit of the fit clearance is 0.10 mm. When the fit clearance is greater than this value, the molten metal collapses at the gap, forming a depression. The misalignment is taken as no more than 0.05 mm, which is one-eighth of the focused spot diameter. When the misalignment is greater than this value, the melting amount on both sides of the joint is uneven, and incomplete fusion appears on one side of the weld.

[0104] Scraping is used to remove the oxide film regenerated on the surface after milling, leaving the surface in an activated state. Laser edge sealing is more sensitive to the surface oxide film than brazing. The critical thickness of the oxide film is taken as 5 nm. Based on the parabolic relationship between film thickness and time, the time required for the oxide film to regenerate to the critical thickness is 2.5 to 2.8 hours. Therefore, the time interval between scraping and laser edge sealing should not exceed 2 hours.

[0105] As an optional embodiment, in step S4, the protective gas is delivered from a nozzle with a diameter of 6 to 8 mm, the angle between the nozzle axis and the welding direction is 30 to 45°, the distance between the nozzle outlet and the outer edge joint is 10 to 15 mm, and the gas flow velocity at the nozzle outlet is 8 to 12 m / s.

[0106] It should be noted that:

[0107] The protective gas flow rate is determined by the nozzle diameter and the outlet velocity, and the calculation formula is:

[0108]

[0109] In the formula, To protect gas flow, The nozzle diameter should be 6–8 mm. The gas velocity at the nozzle outlet is taken as 8–12 m / s. Substituting this into the calculation, the flow rate is 13.6–36.2 L / min, taken as 15–30 L / min. The lower limit of the outlet velocity is determined according to the requirements for molten pool protection. When the velocity is below 8 m / s, air is entrained at the boundary of the protection zone, and the oxygen content on the weld surface increases. The upper limit of the outlet velocity is determined according to the airflow stability. When the velocity is above 12 m / s, the airflow changes from laminar to turbulent and entrains air. The above limits are determined by the measurement results of the change of oxygen content on the weld surface with velocity. The nozzle is arranged with its axis tilted backward, forming an angle of 30–45° with the welding direction, so that the airflow covers the molten pool and the unsolidified weld metal behind it. The distance between the nozzle outlet and the outer edge joint is 10–15 mm. If the distance is too large, the airflow diffusion will be attenuated; if the distance is too small, the nozzle will be contaminated by welding spatter.

[0110] As an optional embodiment, in step S2, a graphite pressure plate is used for clamping and positioning. A clamping pressure of 0.05 to 0.15 MPa is applied to each part to be welded by the graphite pressure plate, and the contact surface between the graphite pressure plate and the part to be welded is coated with boron nitride solder resist.

[0111] It should be noted that:

[0112] The clamping pressure is determined based on the pressure required for the cover plate to elastically flatten. Since the cover plate has flatness errors, the clamping pressure must cause elastic deformation of the cover plate and ensure it fits snugly against the mating surface. The cover plate is calculated using a simply supported thin-plate model at both ends. The formula for calculating the minimum clamping pressure is:

[0113]

[0114] In the formula, Minimum clamping pressure, For the bending stiffness of the cover plate, The maximum flatness error of the cover plate is taken as 0.15mm. The span between adjacent flow channel ribs is taken as 100mm. The formula for calculating the bending stiffness is:

[0115]

[0116] In the formula, The elastic modulus of the aluminum alloy is taken as 7.0 × 10⁻⁶. 10 Pa, The cover plate thickness is taken as 2mm. Let be Poisson's ratio, taken as 0.33. Substitute into the calculation. It is 52.4 N·m. 6.0×10 3 Pa. The clamping pressure also needs to overcome the flow resistance after the solder melts and maintain continuous clamping. Take 8 to 20 times the calculated value, the clamping pressure is 0.048 to 0.12 MPa, take 0.05 to 0.15 MPa. Boron nitride solder resist is used to prevent the overflowing molten solder from bonding the graphite plate to the workpiece.

[0117] As an optional embodiment, in step S5:

[0118] The calibration is performed using a flat plate, and the flatness of the mounting surface of the radiator semi-finished product after calibration is no more than 0.2mm.

[0119] The airtightness test includes airtightness testing and helium mass spectrometry leak detection. The airtightness test is performed by introducing dry gas at a pressure of 0.6 to 0.9 MPa into the flow channel, holding the pressure for 240 to 360 seconds, and determining that the airtightness test is qualified if the pressure drop is not greater than 600 Pa.

[0120] The leak rate of helium mass spectrometry leak detection is no greater than 1×10⁻⁶. -7 Pa·m 3 / s indicates that the helium mass spectrometry leak detection is qualified.

[0121] It should be noted that:

[0122] The airtightness test pressure is determined based on the radiator's operating pressure, and the calculation formula is:

[0123]

[0124] In the formula, For airtightness testing pressure, For safety, we take 1.5. The operating pressure of the radiator flow channel is taken as 0.4–0.6 MPa. Substituting this into the calculation, the airtightness test pressure is 0.6–0.9 MPa. The pressure drop criterion is converted according to the allowable leakage rate, and the calculation formula is:

[0125]

[0126] In the formula, The allowable pressure drop during the pressure holding process, To allow for a leakage rate, take 1×10 -3 Pa·m 3 / s, The pressure holding time is set to 300 seconds. Let the channel volume be 0.5L. Substitute this into the calculation. The value is 600 Pa.

[0127] The leak rate criterion for helium mass spectrometry leak detection is calculated based on the allowable leakage amount over the service life of the radiator, using the following formula:

[0128]

[0129] In the formula, The allowable leak rate for helium mass spectrometry leak detection. The corresponding allowable leakage is the equivalent gas volume that can be leaked during the service life, converted to 300 mL based on the allowable coolant loss. For atmospheric pressure, take 1×10 5 Pa, Based on a service life of 10 years, the calculation is 3.15 × 10⁻⁶. 8 s. Substitute into the calculation, 9.5×10 -8 Pa·m³ / s, take a value not exceeding 1×10 - 7 Pa·m 3 / s. After calibration, the flatness of the mounting surface should not exceed 0.2mm to ensure that the mounting surface fits snugly with the heating element. If the flatness exceeds 0.2mm, the contact thermal resistance will increase.

[0130] The following detailed description of a composite welding method for a heat sink, with reference to specific embodiments, illustrates this method. In the embodiments and comparative examples below, the heat sinks are all water-cooled plate heat sinks. The heat sink base plate and cover plate are made of 3003 aluminum alloy. The dimensions of the heat sink base plate are 240mm × 180mm × 5mm, and the dimensions of the cover plate are 240mm × 180mm × 2mm. The height of the flow channel ribs is 4mm, and the thickness is 2mm. After assembly, the total flow channel volume is 0.5L. The solder sheet is an Al-Si-Mg based aluminum solder sheet, and the liquidus temperature of the solder is 582℃. The vacuum brazing furnace is equipped with a vacuum gauge and a multi-point temperature measuring device. Laser edge sealing welding uses a fiber laser with a focused spot diameter of 0.4–0.5mm.

[0131] Example 1

[0132] This embodiment is implemented according to the following steps.

[0133] S1, Surface pretreatment: The heat sink base plate, flow channel ribs and cover plate are placed in a sodium hydroxide solution with a concentration of 50g / L and a temperature of 58℃ for 5min for alkaline washing, taken out and washed with water, and then placed in a nitric acid solution with a volume fraction of 12% for 2min at room temperature for acid washing, washed with water again, and dried at 100℃ for 30min. Assembly is completed within 6h after drying.

[0134] S2, Assembly and Tightening: The assembly clearance, checked by a feeler gauge, is 0.08 mm. The thickness of the brazing filler metal sheet is determined based on the assembly clearance, calculated as follows:

[0135]

[0136] In the formula, the brazing filler metal compensation coefficient is... The solder thickness is set to 1.31, and the standard brazing filler metal thickness is 0.10 mm. The brazing filler metal coverage area is not less than 95% of the corresponding brazing mating surface area, with an edge inset of 0.8 mm. After assembly, a graphite clamping plate is used for clamping and positioning, with a clamping pressure of 0.10 MPa. The contact surface between the graphite clamping plate and the workpiece to be welded is coated with boron nitride solder resist.

[0137] S3, Vacuum Brazing: Place the assembly to be brazed into a vacuum brazing furnace and evacuate to a vacuum level of 3×10⁻⁶. -3 Pa, heat to 325℃ at 8℃ / min and hold for 20min, the pressure inside the furnace drops back to 1.4 times the pressure at the end of the vacuuming, then heat to 600℃ at 5℃ / min and hold for 15min, cool to 500℃ in the furnace and hold for 15min, then cool to 140℃ in the furnace and remove from the furnace.

[0138] S4, Laser Edge Sealing Welding: Mill 0.5mm on both sides of the inner outer edge joint, with a fit clearance of 0.08mm and a misalignment of 0.03mm. Weld within 1 hour after scraping and cleaning. Laser power is 2500W, welding speed is 45mm / s, defocusing is 0mm, and the linear energy is verified according to the following formula:

[0139]

[0140] The linear energy is in the range of 40–65 J / mm. The shielding gas is argon, the nozzle diameter is 7 mm, the gas velocity at the nozzle outlet is 10 m / s, the angle between the nozzle axis and the welding direction is 40°, and the distance between the nozzle outlet and the outer edge joint is 12 mm. The shielding gas flow rate is verified according to the following calculation formula:

[0141]

[0142] According to the above calculation formula, the flow rate is 3.85 × 10⁻⁶. -4 m 3 / s, which is equivalent to 23.1L / min, so we take 23L / min.

[0143] S5, Post-weld processing and inspection: The semi-finished radiator plate is press-calibrated; the flatness of the mounting surface after calibration is 0.12mm. For airtightness testing, dry air at a pressure of 0.75MPa is introduced and held for 300s; the pressure drop is 210Pa, not exceeding 600Pa, thus passing the airtightness test. The helium mass spectrometry leak detection rate is 3.2×10⁻⁶. -8 Pa·m 3 / s, not greater than 1×10 -7 Pa·m 3 / s, helium mass spectrometry leak detection passed.

[0144] Example 2

[0145] The difference between this embodiment and Embodiment 1 is that the process parameters are selected according to the lower limit of the range, and the following steps are followed.

[0146] S1, Surface pretreatment: Sodium hydroxide solution concentration is 45g / L, temperature is 52℃, alkaline washing for 4min; nitric acid solution volume fraction is 10%, acid washing at room temperature for 1.5min; drying at 85℃ for 40min, and assembly is completed within 20h after drying.

[0147] S2, Assembly and Tightening: The assembly clearance, checked by a feeler gauge, is 0.06 mm. The thickness of the brazing filler metal sheet is determined by the following formula:

[0148]

[0149] The solder filler metal sheet thickness is 0.08 mm (standard specification), and the coverage area is not less than 95% of the corresponding brazing mating surface area, with an inward edge reduction of 0.5 mm. The clamping pressure is 0.06 MPa, and the contact surface is coated with boron nitride solder resist.

[0150] S3, Vacuum Brazing: Vacuum drawn to 4.5 × 10⁻⁶ -3 Pa, heat to 310℃ at 6℃ / min and hold for 28min, then heat to 595℃ at 3.5℃ / min and hold for 20min, cool to 490℃ in the furnace and hold for 18min, then cool to 135℃ in the furnace and remove from the furnace.

[0151] S4, Laser Edge Sealing Welding: Mill 0.4mm on each side of the outer edge joint, with a fit clearance of 0.07mm and a misalignment of 0.04mm. Weld within 0.5 hours after scraping and cleaning. Laser power is 2200W, welding speed is 38mm / s, defocusing distance is -0.5mm, and linear energy is:

[0152]

[0153] The protective gas is helium, the nozzle diameter is 7mm, the nozzle outlet gas velocity is 9m / s, the flow rate is 20.8L / min, and we take 21L / min. The angle between the nozzle axis and the welding direction is 30°, and the distance between the nozzle outlet and the outer edge joint is 10mm.

[0154] S5, Post-weld treatment and inspection: The flatness of the mounting surface after alignment is 0.16mm. The airtightness test pressure is 0.65MPa, held for 300s, with a pressure drop of 380Pa, indicating the airtightness test is qualified. The helium mass spectrometry leak detection rate is 6.5×10⁻⁶. -8 Pa·m 3 / s, helium mass spectrometry leak detection passed.

[0155] Example 3

[0156] The difference between this embodiment and Embodiment 1 is that the flow channel baffles are arranged in series and the process parameters are selected according to the upper limit of the range, and the following steps are followed.

[0157] S1, Surface pretreatment: Sodium hydroxide solution concentration is 58g / L, temperature is 63℃, alkaline washing for 7min; nitric acid solution volume fraction is 14%, acid washing at room temperature for 2.5min; drying at 115℃ for 25min, and assembly is completed within 10h after drying.

[0158] S2, Assembly and Tightening: The assembly clearance, checked by a feeler gauge, is 0.09 mm. The thickness of the brazing filler metal sheet is determined by the following formula:

[0159]

[0160] The solder filler metal sheet thickness is 0.12mm (standard specification), and the coverage area is not less than 95% of the corresponding brazing mating surface area, with an inward edge reduction of 1.0mm. The clamping pressure is 0.14MPa, and the contact surface is coated with boron nitride solder resist.

[0161] S3, Vacuum Brazing: Evacuate to 2×10 -3 Pa, heat to 345℃ at 9℃ / min and hold for 16min, then heat to 605℃ at 5.5℃ / min and hold for 22min, cool to 510℃ in the furnace and hold for 12min, then cool to 148℃ in the furnace and remove from the furnace.

[0162] S4, Laser Edge Sealing Welding: Mill 0.7mm on each side of the outer edge joint, with a fit clearance of 0.09mm and a misalignment of 0.05mm. Weld within 1.5 hours after scraping and cleaning. Laser power is 2900W, welding speed is 55mm / s, defocusing distance is +0.5mm, and linear energy is:

[0163]

[0164] The protective gas is argon, the nozzle diameter is 8mm, the nozzle outlet gas velocity is 9m / s, the flow rate is 27.1L / min, and we take 27L / min. The angle between the nozzle axis and the welding direction is 45°, and the distance between the nozzle outlet and the outer edge joint is 15mm.

[0165] S5, Post-weld treatment and inspection: The flatness of the mounting surface after alignment is 0.19mm. The airtightness test pressure is 0.88MPa, held for 300s, with a pressure drop of 440Pa, indicating the airtightness test is qualified. The helium mass spectrometry leak detection rate is 8.1×10⁻⁶. -8 Pa·m 3 / s, helium mass spectrometry leak detection passed.

[0166] Comparative Example 1

[0167] The difference between this comparative example and Example 1 lies in the reverse welding sequence. First, laser edge sealing welding is performed on the assembly, and then the edge-sealed assembly is placed in a vacuum brazing furnace for brazing according to the temperature profile of Example 1. During the vacuuming stage, the gas escape from the sealed flow channel is obstructed, and the furnace pressure remains higher than the process requirements for an extended period. During the brazing heating stage, the outer weld metal softens and thermal cracks occur under thermal stress. Post-weld sectioning inspection revealed discontinuous brazing filler in the flow channel ribs and two macroscopic cracks in the outer weld. The pressure drop during airtightness testing was 1250 Pa, and the helium mass spectrometry leak detection rate was 4.6 × 10⁻⁶. -6 Pa·m 3 / s, sealing test failed.

[0168] Comparative Example 2

[0169] The difference between this comparative example and Example 1 is that no uniform temperature platform was set up after the brazing and heat preservation process; the assembly was directly cooled from 600°C to 140°C in the furnace before being removed. During the cooling process, the temperature difference across the assembly cross-section was large, causing warping deformation of the thin-walled flow channel structure. Before the alignment, the flatness of the mounting surface was 0.52 mm; after the flat plate alignment, the flatness was 0.27 mm. Three microcracks were found at the edge of the brazed seam using dye penetrant testing, and the helium mass spectrometry leak detection rate was 8.9 × 10⁻⁶. -7 Pa·m 3 / s. The pressure drop during the airtightness test was 410 Pa, which passed the airtightness test, but the leak detection and flatness of the helium mass spectrometry test both failed.

[0170] Performance test results

[0171] The detection results of the above embodiments and comparative examples are summarized in the table below.

[0172]

[0173] As shown in the table above, the pressure drop during airtightness testing in Examples 1 to 3 is no greater than 600 Pa, and the leak rate during helium mass spectrometry leak detection is no greater than 1 × 10⁻⁶. -7 Pa·m 3 / s, the flatness of the mounting surface is no greater than 0.2mm, and all test results are qualified. Comparative Example 1, due to the reverse welding sequence, experienced obstructed venting during the brazing stage and thermal cracks in the outer weld seam, resulting in a failed sealing test. Comparative Example 2, due to the lack of a uniform temperature platform of 480–520℃, resulted in warping and deformation of the assembly and micro-cracks at the brazing seam edge, leading to failures in flatness and helium mass spectrometry leak detection. The comparative results demonstrate that the implementation sequence of vacuum brazing and laser edge sealing welding, as well as the uniform temperature platform during the furnace cooling stage, directly affect the sealing performance and forming accuracy of the radiator.

[0174] Obviously, those skilled in the art can make various modifications and variations to this application without departing from the scope of this application. Therefore, if such modifications and variations fall within the scope of the claims of this application and their equivalents, this application also intends to include such modifications and variations.

Claims

1. A composite welding method for a radiator, characterized in that, Includes the following steps: S1, perform surface pretreatment on the heat sink substrate, flow channel ribs and cover plate to be welded, the surface pretreatment includes alkaline washing and degreasing, acid washing and activation, water washing and drying in sequence; S2, the brazing filler metal sheet is laid between the flow channel baffle and the radiator substrate and between the flow channel baffle and the cover plate. The radiator substrate, flow channel baffle, brazing filler metal sheet and cover plate are assembled and pressed into position according to the flow channel structure to obtain the assembly to be welded. The assembly gap between each brazing mating surface is 0.05 to 0.10 mm. S3. Place the assembly to be welded into the vacuum brazing furnace, evacuate the vacuum, heat it to the brazing temperature according to the preset temperature curve and keep it at the temperature. After the brazing filler metal melts, it fills each brazing mating surface. After cooling with the furnace, it is taken out to obtain an intermediate body with the flow channel sealing surface completed by brazing connection. S4, laser sealing welding is performed on the outer edge seam of the intermediate body. Under the protection of inert gas, welding is continuously performed along the outer edge seam, and a sealing weld is formed between the outer edge of the radiator substrate and the cover plate to obtain the radiator semi-finished product. S5 involves shaping, cleaning, and sealing testing of the semi-finished radiator. Once the sealing test is passed, the finished radiator is obtained.

2. The composite welding method for radiators according to claim 1, characterized in that: In step S1, alkaline washing and degreasing uses a sodium hydroxide solution with a concentration of 40-60 g / L, a treatment temperature of 50-65℃, and a treatment time of 3-8 min; Acid washing and activation are performed using a 10%–15% (v / v) nitric acid solution at room temperature for 1–3 min. The drying temperature is 80-120℃, the drying time is 20-40 minutes, and the time interval between drying and assembly in step S2 does not exceed 24 hours.

3. The composite welding method for the radiator according to claim 1 or 2, characterized in that: The heat sink base plate and cover plate are made of 3003 aluminum alloy; In step S2, the solder sheet is an Al-Si-Mg based aluminum solder sheet with a thickness of 0.08–0.12 mm. The area of ​​the brazing filler metal sheet shall not be less than 95% of the area of ​​the corresponding brazing mating surface, and the edge of the brazing filler metal sheet shall be recessed by 0.5 to 1.0 mm relative to the edge of the corresponding brazing mating surface.

4. The composite welding method for the radiator according to claim 3, characterized in that: In step S3, the vacuum level inside the vacuum brazing furnace shall not exceed 5 × 10⁻⁶. -3 Pa; The preset temperature curve is as follows: heat up to 300-350℃ at a first heating rate of 5-10℃ / min and hold for 15-30min, then heat up to the brazing temperature at a second heating rate of 3-6℃ / min and hold for 10-25min. The brazing temperature is 33-53℃ lower than the solidus temperature of 3003 aluminum alloy, and the brazing temperature is 590-610℃.

5. The composite welding method for the radiator according to claim 4, characterized in that, The furnace cooling in step S3 includes: first cooling the furnace to 480-520°C and holding it at that temperature for 10-20 minutes, then cooling the furnace to the furnace exit temperature and removing the furnace, with the furnace exit temperature not exceeding 150°C.

6. The composite welding method for the radiator according to claim 1, characterized in that, In step S4: Laser edge sealing welding uses a fiber laser with a focused spot diameter of 0.4–0.5 mm, a laser power of 2000–3000 W, a welding speed of 35–60 mm / s, and a defocusing amount of -1–+1 mm. The inert gas is argon or helium, and the protective gas flow rate is 15–30 L / min.

7. The composite welding method for a radiator according to claim 6, characterized in that, In step S4, before laser edge sealing welding, the outer edge joint of the intermediate body is trimmed: the outer edge joint is milled by 0.3 to 0.8 mm on both sides so that the fit gap of the outer edge joint is no more than 0.10 mm and the misalignment is no more than 0.05 mm. After repair, the outer edge seams are scraped and cleaned. The time interval between scraping and cleaning and laser edge sealing welding shall not exceed 2 hours.

8. The composite welding method for the radiator according to claim 6 or 7, characterized in that, In step S4, the protective gas is delivered from a nozzle with a diameter of 6-8 mm, the angle between the nozzle axis and the welding direction is 30-45°, the distance between the nozzle outlet and the outer edge joint is 10-15 mm, and the gas velocity at the nozzle outlet is 8-12 m / s.

9. The composite welding method for a radiator according to any one of claims 1 to 5, characterized in that, In step S2, a graphite pressure plate is used for clamping and positioning. A clamping pressure of 0.05 to 0.15 MPa is applied to each part to be welded by the graphite pressure plate. The contact surface between the graphite pressure plate and the part to be welded is coated with boron nitride solder resist.

10. The composite welding method for a radiator according to claim 1, characterized in that, In step S5: The calibration is performed using a flat plate, and the flatness of the mounting surface of the radiator semi-finished product after calibration is no more than 0.2mm. The airtightness test includes airtightness testing and helium mass spectrometry leak detection. The airtightness test is performed by introducing dry gas at a pressure of 0.6 to 0.9 MPa into the flow channel, holding the pressure for 240 to 360 seconds, and determining that the airtightness test is qualified if the pressure drop is not greater than 600 Pa. The leak rate of helium mass spectrometry leak detection is no greater than 1×10⁻⁶. -7 Pa·m 3 / s indicates that the helium mass spectrometry leak detection is qualified.